SRSF6-regulated alternative splicing that promotes tumour progression offers a therapy target for colorectal cancer. Issue 1 (7th November 2017) - Wan, Ledong; Yu, Wenying; Shen, Enhui; Sun, Wenjie; Liu, Yuan; Kong, Jianlu; Wu, Yihua; Han, Fengyan; Zhang, Lei; Yu, Tianze; Zhou, Yuwei; Xie, Sunzhe; et al.
Abstract : Objective: To investigate the molecular function of splicing factor SRSF6 in colorectal cancer (CRC) progression and discover candidate chemicals for cancer therapy through targeting SRSF6. Design: We performed comprehensive analysis for the expression of SRSF6 in 311 CRC samples, The Cancer Genome Atlas and Gene Expression Omnibus (GEO) database. Functional analysis of SRSF6 in CRC was performed in vitro and in vivo . SRSF6-regulated alternative splicing (AS) and its binding motif were identified by next-generation RNA-sequencing and RNA immunoprecipitation sequencing (RIP-seq), which was validated by gel shift and minigene reporter assay. ZO-1 exon23 AS was investigated to mediate the function of SRSF6 in vitro and in vivo . Based on the analysis of domain-specific role, SRSF6-targeted inhibitor was discovered de novo by virtual screening in 4855 FDA-approved drugs and its antitumour effects were evaluated in vitro and in vivo . Results: SRSF6 was frequently upregulated in CRC samples and associated with poor prognosis, which promoted proliferation and metastasis in vitro and in vivo . We identified SRSF6-regulated AS targets and discovered the SRSF6 binding motif. Particularly, SRSF6 regulates ZO-1 aberrant splicing to function as an oncogene by binding directly to its motif in the exon23. Based on the result that SRSF6 RRM2 domain plays key roles in regulating AS and biological function, indacaterol, a β2-adrenergic receptor agonist approved for chronic obstructive pulmonary disease treatment, is identified as the inhibitor of SRSF6 to suppress CRC tumourigenicity. Conclusions: SRSF6 functions the important roles in mediating CRC progression through regulating AS, and indacaterol is repositioned as an antitumour drug through targeting SRSF6. Accession numbers: The accession numbers for sequencing data are SRP111763 and SRP111797.